A reconfigurable multi-terrain adaptive casualty transport aid base on Watt II six-bar linkage for industrial environment - Jiao, Zongqi; Wang, Haibin; Fei, Cuizhi; Wang, Liang; Yuan, Jincan; Meng, Qiaoling; Lu, Xuhua (Frontiers in Bioengineering and Biotechnology, 2024)
This paper introduces the design and development of the Reconfigurable Multi-Terrain Adaptive Casualty Transport Aid (RMTACTA). This innovative casualty transport aid is built upon the Watt II six-bar linkage, capable of undergoing structural reconfiguration to provide six modes of motion: stretcher mode, stretcher vehicle mode, folding mode, gangway-passing mode, obstacle-crossing mode, and upright mode. These modes enable rapid and stable casualty transport by rescuers across challenging terrains in industrial environments. A detailed mechanical design of the aid is provided, alongside a kinematic model of the reconfigurable framework based on mechanism decomposition principles. Additionally, the locomotion of the transport aid in correlate on with the transformation of the reconfigurable framework are analyzed. Numerical simulations of the proposed reconfigurable framework are conducted, integrating a parametric study associated with driving conditions, resulting in the optimization of structural parameters. Furthermore, a static analysis of the reconfigurable frame characterizes the necessary driving forces. Consequently, a prototype of the RMTACTA has been developed and undergone field trials, demonstrating its effectiveness in transporting casualties across diverse terrains.